COMORBID PATIENT IN GASTROENTEROLOGY: INDIVIDUAL APPROACH - I. G. Bakulin; S. A. Sayganov; M. I. Skalinskaya; E. V. Skazyayeva; I. V. Lapinskii (Столичная издательская компания, 2018)
In connection with the increase in the life expectancy of modern people, in recent years questions of comorbid conditions have become of great interest among clinicians. Comorbidity, which increases with the age of patients, may reduce their adherence to treatment, including because of the use of multicomponent regimens of therapy, which in turn leads to a decrease in the effectiveness of the treatment. In this regard, there is a need for individual adjustment of therapeutic regimens with minimal drug interactions. In the article, a clinical case is presented as a therapeutic and diagnostic algorithm for a comorbid patient with combination of the digestive and cardiovascular systems disorders. The choice of therapeutic-diagnostic algorithm was based on modern Russian and foreign recommendations. The emphasis is on the stratification of both gastroenterological and cardiologic risk factors, and the strategy for choosing proton pump inhibitors, depending on clinical dynamics. The rationale for the replacement of proton pump inhibitors is given, taking into account the probability of inter-drug interactions in a patient with high cardiovascular risk taking acetylsalicylic acid and having a high risk of gastrointestinal tract bleeding. The data of several large meta-analyzes reflecting approaches to reduce the risk of gastropathy associated with non-steroidal anti-inflammatory drugs due to the use of disaggregants as well as eradication therapy in these patients are presented.